PENGARUH UPAH DAN INVESTASI TERHADAP KETIMPANGAN PENDAPATAN DAN KESEJAHTERAAN MASYARAKAT KABUPATEN KOTA DI PROVINSI BALI (Universitas Udayana, 2022)
Equitable and equitable economic development mandates development programs that encourage increased regional economic growth, eliminate inequality and can improve community welfare in a sustainable manner. This study aims to determine the effect of wages and investment on income inequality and the welfare of the district/city community in Bali Province. The source of the data used in this study is panel data of 63 data from 2015-2021 in 9 districts/cities in Bali, the method of collecting data is non-participant observation by observing documents related to the research. The data analysis technique used is path analysis technique. The results show that wages have a negative and significant effect on income inequality, while investment has a positive and significant effect on income inequality in the districts/cities of Bali Province. Wages and investment have a positive and significant effect on people's welfare, while income inequality has a positive but not significant effect on people's welfare in the districts/cities of Bali Province. Income inequality does not mediate the effect of wages and investment on welfare Keywords: wages, investment, inequality, welfare.